Whom to blame for metastasis, the epithelial-mesenchymal transition or the tumor microenvironment? - M Pietilä; J Ivaska; SA Mani (ELSEVIER IRELAND LTD, 2022)
Changes in the tumor microenvironment (TME) can trigger the activation of otherwise non-malignant cells to become highly aggressive and motile. This is evident during initial tumor growth when the poor vascularization in tumors generates hypoxic regions that trigger the latent embryonic program, epithelial-to-mesenchymal transition (EMT), in epithelial carcinoma cells (e-cars) leading to highly motile mesenchymal-like carcinoma cells (m-cars), which also acquire cancer stem cell properties. After that, specific bidirectional interactions take place between m-cars and the cellular components of TME at different stages of metastasis. These interactions include several vicious positive feedback loops in which m-cars trigger a phenotypic switch, causing normal stromal cells to become pro-tumorigenic, which then further promote the survival, motility, and proliferation of m-cars. Accordingly, there is not a single culprit accounting for metastasis. Instead both m-cars and the TME dynamically interact, evolve and promote metastasis. In this review, we discuss the current status of the known interactions between m-cars and the TME during different stages of metastasis and how these interactions promote the metastatic activity of highly malignant m-cars by promoting their invasive mesenchymal phenotype and CSC properties. (C) 2016 Elsevier Ireland Ltd. All rights reserved.